Fecundity of Mylossoma duriventre (Silver Mylossoma) in Ucayali during the 2011-2012 reproductive cycle - Zaldívar E., Javier (2016)
Mylossoma duriventre «Silver Mylossoma» is a fish of the family Characidae, commercially exploited for human consumption in the region of Ucayali, Peru. The aim of the present study was to improve the reproductive knowledge of the species in relation to fecundity. Forty nine specimens were collected from landings in Pucallpa during the 2011-2012 reproductive cycle. Measurements of total length (LT), total weight (PT) and the weight of gonads (PGon) of each fish were recorded. Subsamples of gonads were taken for oocyte counting to determine fecundity applying the simple linear regression equation F = a + bx, where F = fecundity, x = total length, total body weight or ovarian weight, a is the intercept and b the rate of increase in fecundity in relation to the variables in the study. The mean absolute fecundity was estimated in 68 280 oocytes which corresponds to an average LT of 21.3 cm (range: 10 749 to 134 665 oocytes in specimens with sizes varying from 18.5 to 28.0 cm). The best correlation based on regression analysis between the number of oocytes with LT, PT and PGon was with the latter, where the equation was N.° of oocytes = 1618.1 PGon + 11735 (r2=0.7917; p<0.05).